2022
DOI: 10.1007/s00259-022-05794-w
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT in indeterminate thyroid nodules: cost-utility analysis alongside a randomised controlled trial

Abstract: Purpose To evaluate cost-effectiveness of an [18F]FDG-PET/CT-driven diagnostic workup as compared to diagnostic surgery, for thyroid nodules with Bethesda III/IV cytology. [18F]FDG-PET/CT avoids 40% of futile diagnostic surgeries for benign Bethesda III/IV nodules. Methods Lifelong societal costs and quality-adjusted life years (QALYs) were assessed for 132 patients participating in a randomised controlled multicentre trial comparing [18F]FDG-PET/CT to dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Our previous intention-to-treat analysis of the EQ-5D-5L results demonstrated non-inferiority of an FDG-PET/CT-driven workup with regard to general HRQoL based on QALYs ( 6 , 8 ). For the current comprehensive HRQoL study, a per-protocol analysis with exclusion of crossovers was considered most appropriate, despite its known drawbacks with regard to bias ( 40 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our previous intention-to-treat analysis of the EQ-5D-5L results demonstrated non-inferiority of an FDG-PET/CT-driven workup with regard to general HRQoL based on QALYs ( 6 , 8 ). For the current comprehensive HRQoL study, a per-protocol analysis with exclusion of crossovers was considered most appropriate, despite its known drawbacks with regard to bias ( 40 ).…”
Section: Discussionmentioning
confidence: 91%
“…Our recent randomised controlled multicentre trial confirmed that a negative FDG-PET/CT scan accurately rules out malignancy with a 94% sensitivity, avoiding 40% of futile diagnostic surgeries for benign nodules ( 6 , 7 ). Moreover, FDG-PET/CT proved cost-effective in a Dutch setting, with lower societal lifelong costs while maintaining the long-term health-related quality of life (HRQoL) in patients undergoing FDG-PET/CT-driven management as compared to routine diagnostic surgery or molecular testing ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the consequential additional health care expenses had no impact on cost-effectiveness of [ 18 F]FDG-PET/CT, incidental findings can be limited by performing partial-body imaging only. 18 , 21 …”
Section: Discussionmentioning
confidence: 99%
“… 18–20 With a 94% sensitivity, [ 18 F]FDG-PET/CT accurately excludes malignancy in ITN and cost-effectively avoids 40% of futile diagnostic surgeries for benign nodules. 18 , 21 The specificity of [ 18 F]FDG-PET/CT is only 40% as many noncancerous ITN also show increased uptake of [ 18 F]FDG. 18 …”
Section: Introductionmentioning
confidence: 99%